Extractive Fermentation of Lactic Acid in Lactic Acid Bacteria Cultivation: A Review - Othman, Majdiah; Ariff, Arbakariya B.; Rios-Solis, Leonardo; Halim, Murni (Frontiers in Microbiology, 2017)
Lactic acid bacteria (LAB) are industrially important microorganisms recognized for their fermentative ability mostly in their probiotic benefits as well as lactic acid production for various applications. Nevertheless, lactic acid fermentation often suffers end-product inhibition which decreases the cell growth rate. The inhibition of lactic acid is due to the solubility of the undissociated lactic acid within the cytoplasmic membrane and insolubility of dissociated lactate, which causes acidification of cytoplasm and failure of proton motive forces. This phenomenon influences the transmembrane pH gradient and decreases the amount of energy available for cell growth. In general, the restriction imposed by lactic acid on its fermentation can be avoided by extractive fermentation techniques, which can also be exploited for product recovery.